2003
DOI: 10.1001/jama.289.18.2407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Practice-Based Strategy on Test Ordering Performance of Primary Care Physicians

Abstract: N MANY COUNTRIES, THE NUMBER OF diagnostic tests ordered by primary care physicians is growing, while according to established evidence-based guidelines, many of these tests are seen as unnecessary. [1][2][3] Possible explanations are test ordering routines that are difficult to change, a more defensive attitude among primary care physicians out of fear of medical errors, or a lack of knowledge about the appropriate use of tests. [4][5][6][7] Moreover, patients more actively ask for tests and often attach grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
130
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 16 publications
1
130
0
2
Order By: Relevance
“…Indeed, a recent randomized controlled multicenter trial, which targeted specific patient disorders and assessed whether appropriate testing guidelines were being followed, showed only a modest effect of intervention (33 ). The success of intervention in the present study could stem from several factors.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, a recent randomized controlled multicenter trial, which targeted specific patient disorders and assessed whether appropriate testing guidelines were being followed, showed only a modest effect of intervention (33 ). The success of intervention in the present study could stem from several factors.…”
Section: Discussionmentioning
confidence: 61%
“…Direct costs include test and operator costs, whereas indirect costs are broader including consequences of test results in terms of treatment, implications of inaccurate test results, and longer-term costs in terms of patient outcome. A number of studies have found that clinical guidelines and policy recommendations affect doctors' test ordering, generally by reducing inappropriate test ordering [8,11,12,18,19,21,25,35].…”
Section: Policy and Organization-related Factorsmentioning
confidence: 99%
“…In one multicenter randomized trial with a block design, this strategy was indeed found to have a favorable effect on physicians' testordering behavior. 22 A cost analysis of the new strategy and a process evaluation showed that it was a cost-efficient and feasible tool for improvement of physicians' test-ordering behavior. 23,24 This article determines the effects of this innovative, multifaceted strategy, compared with a classic feedback strategy, to assess the added value of the small-group quality improvement meetings.…”
Section: Introductionmentioning
confidence: 99%